Analysis of the substance scanning test results of non- alcohol substance abusers who admitted an university hospital - Okan, Aslıhan; Atlı, Abdullah; Alhan, Cafer; Demir, Süleyman; Kaya, Mehmet Cemal; Sır, Aytekin (Journal of Dependence, 2016)
Background: Urine toxicological analysis is one of the objective procedures as rapidly investigate for the identifies substance use, including initial diagnosis, with treatment plan for substance abusers and compliance with treatment. Toxicological analysis for legal purposes primarily aims to detect illegal or banned drug and substance use in a variety of situations. The aim of this study was to evaluate the results of toxicological analysis of patients who admitted to Dicle University Hospital with prediagnosis of non-alcohol substance use. Method: The participants of the study included 167 patients who admitted voluntarily or by request of the family to outpatient psychiatry department of Dicle Medicine Faculty and who were asked for urine toxicology screen from January to December 2014. The files of each participants were carefully evaluated with retrospective analysis by the experienced researchers. Results: 12.0 % (n=20) of the participants were female, and 88.0 % (n=147) of them were male. 44.9 % of participants (n=75) had urine positive whereas the 55.1% of patients (n=92) had urine negative for substance use. The most common substance use was Marijuana (88%, n=66) followed by 3,4-methylenedioxymethamphetamine (MDMA) (18.6%,n=14), Methamphetamine (Meth) (16.0%,n=12), opioids (5.3%, n=4), Barbiturates (4.0%,n=3) and Phencyclidine (PCP) (2.7%, n=2), respectively. Results showed that 37.3% (n=28) of patients were using polysubstance, whereas the 62.7% (n=47) of patients were using only one substance. One particular substance usage ratio was: 43 participants were using Marijuana, 2 participants were using Meth, 1 participant was using Barbiturates, and 1 participant was using MDMA. Discussion and Conclusion: According to toxicological analysis, substance use were not found in 55.1 % of the participants. The most common substance use was marijuana in toxicological analysis. In addition, other substances with stimulant effect were among the commonly used substances, including the meth amphetamine, amphetamine and also phencyclidine, barbiturates, opioid and its derivatives. Numerous environmental factors may have affected this growing rates of increases in marijuana abuse and growing dependence prevalence. As a result, substance abuse is an important public health problem. Increase in substance use rate and easy access to substances have reached a worrying level. Our region carries a significant risk in terms of the substance abuse and particularly for marijuana. In light of these results, protective actions related to use of the substances should be increased besides the emergency health care needs in Diyarbakir.